Linking hydrologic signatures to hydrologic processes: A review - McMillan, Hilary (Hydrological processes, 2020)
Hydrologic signatures are metrics that quantify aspects of streamflow response. Linking signatures to underlying processes enables multiple applications, such as selecting hydrologic model structure, analysing hydrologic change, making predictions in ungauged basins, and classifying watershed function. However, many lists of hydrologic signatures are not process‐based, and knowledge about signature‐process links has been scattered among studies from experimental watersheds and model selection experiments. This review brings together those studies to catalogue more than 50 signatures representing evapotranspiration, snow storage and melt, permafrost, infiltration excess, saturation excess, groundwater, baseflow, connectivity, channel processes, partitioning, and human alteration. The review shows substantial variability in the number, type, and timescale of signatures available to represent each process. Many signatures provide information about groundwater storage, partitioning, and connectivity, whereas snow processes and human alteration are underrepresented. More signatures are related to the seasonal scale than the event timescale, and land surface processes (ET, snow, and overland flow) have no signatures at the event scale. There are limitations in some signatures that test for occurrence but cannot quantify processes, or are related to multiple processes, making automated analysis more difficult. This review will be valuable as a reference for hydrologists seeking to use streamflow records to investigate a particular hydrologic process or to conduct large‐sample analyses of patterns in hydrologic processes. This paper provides a comprehensive review of how hydrologic signatures (metrics of streamflow response) provide information about underlying hydrological processes. It catalogues and analyses more than 50 signatures from experimental and modelling studies. It is a valuable reference for hydrologists seeking to use streamflow records to investigate processes in a watershed, or to conduct large‐sample analyses of patterns in hydrologic processes.